2005
DOI: 10.1088/0957-4484/17/2/002
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of alumina nanowire formation from porous anodic alumina membrane via the droplet etching method

Abstract: We report the first direct observation of the formation process of an alumina nanowire (ANW) array from a porous anodic alumina (PAA) membrane employing a simple droplet etching method, not a general immersion etching method, using field emission scanning electron spectroscopy (FESEM). The PAA membrane is prepared by the two-step anodization method and subsequent lift-off process. The surface view SEM images of the PAA membrane show an array of highly ordered hexagonal pore distribution within the domains of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Considering the layer structure of pores in the PAM, the diffusion distance corresponds to the thickness of the contaminated alumina layer of the PAM. 16 Hence, we suggest that the Pb and Ti elements diffused through the oxygen vacancies in the contaminated alumina layer of pores in the PAM. …”
Section: -4mentioning
confidence: 79%
See 1 more Smart Citation
“…Considering the layer structure of pores in the PAM, the diffusion distance corresponds to the thickness of the contaminated alumina layer of the PAM. 16 Hence, we suggest that the Pb and Ti elements diffused through the oxygen vacancies in the contaminated alumina layer of pores in the PAM. …”
Section: -4mentioning
confidence: 79%
“…1(c)). As the amorphous, PAM was selectively etched away, 16 the PZT nanotubes were released as individual PZT nanotubes. Figure 1(f) shows an FETEM image of an individual PZT nanotube released in this manner.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, alumina nanowires and nanotubes can be used as catalyst supports, radar transparent structures, and antenna windows because of their large surface areas and highly electropositive surfaces [10]. Previously, alumina nanowires were synthesized through various techniques, including coating of carbon nanotubes with aluminum isopropoxide [11], vapor-liquidsolid growth, hydrothermal synthesis [12], arc discharge, electrochemical deposition [13], and chemical etching of porous anodic alumina film [14]. Among them, chemical etching is a simple and low-cost method for producing alumina nanostructures [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They offer promising technological applications, which are attributed to their high strength, corrosion resistance, chemical stability, low thermal conductivity and good electrical insulation [1]. Moreover, alumina nanowires have become a thrilling field of study because they are useful for water purification filter technology owing to their large surface area and highly electropositive surface [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical etching of a porous anodic alumina membrane is considered as an easy and cost effective way to fabricate uniform diameter alumina nanowires [2]. In this sense, several groups of authors reported different alumina nanostructures that were fabricated via a simple etching method in NaOH [4][5][6][7] or in a chromic and phosphoric acid solution [1,7].…”
Section: Introductionmentioning
confidence: 99%